The E3 ubiquitin ligase NEDD4 is an LC3-interactive protein and regulates autophagy. Issue 3 (4th March 2017) - Sun, Aiqin; Wei, Jing; Childress, Chandra; Shaw, John H.; Peng, Ke; Shao, Genbao; Yang, Wannian; Lin, Qiong
ABSTRACT: The MAP1LC3/LC3 family plays an essential role in autophagosomal biogenesis and transport. In this report, we show that the HECT family E3 ubiquitin ligase NEDD4 interacts with LC3 and is involved in autophagosomal biogenesis. NEDD4 binds to LC3 through a conserved WXXL LC3-binding motif in a region between the C2 and the WW2 domains. Knockdown of NEDD4 impaired starvation- or rapamycin-induced activation of autophagy and autophagosomal biogenesis and caused aggregates of the LC3 puncta colocalized with endoplasmic reticulum membrane markers. Electron microscopy observed gigantic deformed mitochondria in NEDD4 knockdown cells, suggesting that NEDD4 might function in mitophagy. Furthermore, SQSTM1 is ubiquitinated by NEDD4 while LC3 functions as an activator of NEDD4 ligase activity. Taken together, our studies define an important role of NEDD4 in regulation of autophagy.